FATP2-targeted therapies — A role beyond fatty liver disease. (November 2020) - Qiu, Peishan; Wang, Haizhou; Zhang, Mengna; Zhang, Meng; Peng, Ruyi; Zhao, Qiu; Liu, Jing
Graphical abstract: Abstract: Fatty acid transport protein 2 (FATP2) is a multifunctional protein whose specific function is determined by the type of located cell, its intracellular location, or organelle-specific interactions. In the different diseases setting, a newfound appreciation for the biological function of FATP2 has come into view. Two main functions of FATP2 are to activate long-chain fatty acids (LCFAs) as a very long-chain acyl-coenzyme A (CoA) synthetase (ACSVL) and to transport LCFAs as a fatty acid transporter. FATP2 is not only involved in the occurrence of nonalcoholic fatty liver disease (NAFLD) and type 2 diabetes mellitus (T2DM), but also plays an important role in lithogenic diet-induced cholelithiasis, the formation of cancer tumor immunity, the progression of chronic kidney disease (CKD), and the regulation of zoledronate-induced nephrotoxicity. Herein, we review the updated information on the role of FATP2 in related diseases. In particular, we discuss the new functions of FATP2 and propose that FATP2 is a potential clinical biomarker and therapeutic target. In conclusion, regulatory strategies for FATP2 may bring new treatment options for cancer and lipid metabolism-related disorders.